2008
DOI: 10.1111/j.1440-1797.2008.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Cytochrome P450 enzyme, and transport protein mediated herb–drug interactions in renal transplant patients: Grapefruit juice, St John's Wort – and beyond! (Review Article)

Abstract: SUMMARY:Aim: To survey the evidence for plant-products to modify cytochrome P450 enzyme, and transport protein mediated drug metabolism in renal transplant patients. Methods: A literature search was performed to identify "in vitro" and "in vivo" research on plant-products that might cause overdosage or loss of efficacy of immunosuppressive drugs in transplant patients by the interaction mechanisms already characterized for grapefruit juice and St. John's Wort. Results: The interaction mechanisms of St. John's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 101 publications
(135 reference statements)
0
67
0
4
Order By: Relevance
“…Cytochrome P450 (CYP) monooxygenases are probably the most important classes of enzymes in hepatic drug metabolism (Liu et al, 2006) and the list of herbal medicines with a potential for modifying drug bioavailability by inhibition or stimulation of CYP450 enzymes seems endless. For example, St John's wort increases the activity of the CYP3A4 and may lead to a reduction in plasma concentration of a number of medicines, including cyclosporin, statins and hormonal contraceptives (Novack, 2008).…”
Section: "Mixing Herbs With Allopathic Medicines We Do Not Know How Imentioning
confidence: 99%
“…Cytochrome P450 (CYP) monooxygenases are probably the most important classes of enzymes in hepatic drug metabolism (Liu et al, 2006) and the list of herbal medicines with a potential for modifying drug bioavailability by inhibition or stimulation of CYP450 enzymes seems endless. For example, St John's wort increases the activity of the CYP3A4 and may lead to a reduction in plasma concentration of a number of medicines, including cyclosporin, statins and hormonal contraceptives (Novack, 2008).…”
Section: "Mixing Herbs With Allopathic Medicines We Do Not Know How Imentioning
confidence: 99%
“…[18] In the present study, felodipine AUC and K a values were reduced, while clearance was increased for the groups co-administered with paw paw and pumpkin (ugu) vegetable extract. Studies by [19,20] revealed that tangeretin, a flavonoid found in high levels in tangerine juice, stimulates CYP3A4 activity. It was shown to be a potent region-selective stimulator of midazolam 1 ′ -hydroxylation by human liver microsomes CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…Bir Sit P450 3A4 inhibitörü olup, diğer Sit P450 izozimleri üzerine etkisiz olduğu bildirilmiştir [35].…”
Section: Rubiaceaeunclassified